Basic Algebra Test: Simplifying Expressions! Trivia Quiz

5 Questions | Total Attempts: 28

SettingsSettingsSettings
Please wait...
Basic Algebra Test: Simplifying Expressions! Trivia Quiz

.


Questions and Answers
  • 1. 
    Simplify the following expressions 1)  a + a + a = [Blank] 2)  2t + t = [Blank] 3)  2c + 3c = [Blank] 4)  5p + 2p = [Blank] 5)  4f + 9f = [Blank] 6)  7u - 3u = [Blank] 7)  6g - 2g = [Blank] 8)  9w - 2w = [Blank] 9)  5y - y = [Blank] 10)  5r - 2r = [Blank]
  • 2. 
    Simplify the following expressions 1) d + 2d + 5d = [Blank] 2)  4r + 7r + 8r = [Blank]  3)  9a + a + 6a = [Blank] 4)  -6g + 2g + 9g = [Blank] 5) 6y + 3y - 8y = [Blank] 6) -7u - 2u + 6u = [Blank] 7)  3w + 6w + 2w = [Blank] 8)  9b + 6b + 8b = [Blank] 9)  4t + 3t - 5t = [Blank] 10) 8p + 6p - 9p = [Blank]
  • 3. 
    Simplify the following expressions (answer with no space between the terms) 1)  2a + 3b + 4a = [Blank] 2) 7v + 2u + 4v = [Blank] 3)  9f + 4g + 2f = [Blank] 4)  7c + 8d + 5c = [Blank] 5) 9u - 2u + 6v = [Blank] 6) 5a - 4a + 2b = [Blank] 7) 7j - 4j + 7k = [Blank] 8) 9s - 6s + 3t = [Blank] 9) 6f + 9g - 2f = [Blank] 10) 9p - 5q - 2p = [Blank]
  • 4. 
    Simplify the following expressions (leave no space in your answers) 1) 3a + 4b + 6a + 3b = [Blank] 2) 7m + 6n + 4m + 8n = [Blank]  3) 6p + 4q + 3p + 7q = [Blank] 4) 7y + 2x + 9y + 2x = [Blank] 5) 8u + 3v + 2u + 7v = [Blank] 6) 4u + 3v + 12u - 2v = [Blank] 7) 6y + 7h - 2y + 3h = [Blank] 8) 4e + 3d + 5e - 5d = [Blank] 9) 5t + 4f - 3t - 5f = [Blank] 10) 6u + 3s - 4u - 7s = [Blank] 11) 6y - 3g + 2y - 4g = [Blank] 12) 8q - 7p - 6q - 3p = [Blank]  13) 4u - 7y + 11u - 5y = [Blank] 14) 5x - 7y + 3x - 4y = [Blank] 15) 12b - 4c + 3b - 2c = [Blank] 16) 6q + 12r + 3q - 11r = [Blank] 17) 6r - 5t - 8r - 4t = [Blank] 18) -3a +4b -5a -7b = [Blank] 19) 10a -4b -12a -3b = [Blank] 20) -5a -6b -3a -6b = [Blank]
  • 5. 
    Expand the following brackets example:  3(2a + 5) = 6a+15   1) 3(2f + 4) = [Blank] 2) 2(3a + 4) = [Blank]  3) 4(2e + 5) = [Blank] 4) 3(4t + 2) = [Blank] 5) 2(4y + 7) = [Blank] 6) 4(3r - 5) = [Blank] 7) 7(2a + 3) = [Blank] 8) 4(3j - 6) = [Blank] 9) 5(2q - 9) = [Blank] 10) 7(6y - 8) = [Blank] 11) 3(2e + 5t) = [Blank] 12) 5(6y + 2w) = [Blank] 13) 3(2s - 4t) = [Blank] 14) 7(6k - 2v) = [Blank] 15) 9(2w - e) = [Blank]